Methylation-directed glycosylation of chromatin factors represses retrotransposon promoters - Boulard, Mathieu; Rucli, Sofia; Edwards, John R.; Bestor, Timothy H. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
The mechanisms by which methylated mammalian promoters are transcriptionally silenced even in the presence of all of the factors required for their expression have long been a major unresolved issue in the field of epigenetics. Repression requires the assembly of a methylation-dependent silencing complex that contains the TRIM28 protein (also known as KAP1 and TIF1 beta), a scaffolding protein without intrinsic repressive or DNA-binding properties. The identity of the key effector within this complex that represses transcription is unknown. We developed a methylation-sensitized interaction screen which revealed that TRIM28 was complexed with O-linked beta-N-acetylglucosamine transferase (OGT) only in cells that had normal genomic methylation patterns. OGT is the only glycosyltransferase that modifies cytoplasmic and nuclear protein by transfer of N-acetylglucosamine (O-GlcNAc) to serine and threonine hydroxyls. Whole-genome analysis showed that O-glycosylated proteins and TRIM28 were specifically bound to promoters of active retrotransposons and to imprinting control regions, the two major regulatory sequences controlled by DNA methylation. Furthermore, genome-wide loss of DNA methylation caused a loss of O-GlcNAc from multiple transcriptional repressor proteins associated with TRIM28. A newly developed Cas9-based editing method for targeted removal of O-GlcNAc was directed against retrotransposon promoters. Local chromatin de-GlcNAcylation specifically reactivated the expression of the targeted retrotransposon family without loss of DNA methylation. These data revealed that O-linked glycosylation of chromatin factors is essential for the transcriptional repression of methylated retrotransposons.